Trends in OEM manufacturing strategy in Malaysian furniture industry - Liow, Ting Yi (2019)
Original Equipment Manufacturing (OEM) or contract-manufacturing strategy has been the predominant strategy employed throughout the Malaysian furniture industry over decades. However, this strategy is no longer well-suited when the industry is gradually losing its competitiveness with the emergence of low cost producers such as China and Vietnam due to rising cost and dwindling supply of resources. Besides, the innovation ratio of Malaysian furniture industry has been on significant decline, reflects that the industry is struggling with original design manufacturing (ODM) and original brand manufacturing (OBM) strategies, which are driven by value addition and innovation. In this study, we seek to examine the growth trend in OEM strategy in Malaysian furniture industry. This study used quantitative research approach where the primary data was collected via questionnaire survey and was analyzed. The main findings of this study revealed that, currently over reliance on OEM strategy by the industry is due to the workforce factor. The analysis on the challenges of lack of innovation showed that the manufacturers are very financially concerned and “products acceptance” concerned. These challenges were found to be the biggest hindrance and concern for the industry to involve in innovation activities.